2007
DOI: 10.1096/fj.07-9034com
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells support angiogenesis and promote lesion growth in a murine model of endometriosis

Abstract: Endometriosis affects 10-15% of women and is associated with pelvic pain and infertility. Angiogenesis plays an essential role in its pathogenesis. Dendritic cells (DCs) were recently implicated in supporting tumor angiogenesis. As both tumors and endometriosis lesions depend on angiogenesis, we investigated the possibility that DCs may also play a role in endometriosis. We induced endometriosis in 8-wk-old female C57BL/6 mice by implantation of autologous endometrium into the peritoneal cavity. We observed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 30 publications
3
85
2
Order By: Relevance
“…In support to this model, the peritoneal fluid of patients with endometriosis interferes with in vitro differentiation of precursors challenged with recombinant cytokines, favoring their differentiation toward macrophages 9 and immature dendritic cells injected into endometriotic mice intraperitoneally actively migrate and infiltrate ectopic endometrial lesions, where they contribute to lesions further development. 49 In conclusion, our findings indicate that the peritoneal environment controls the differentiation of macrophage precursors, committing them toward an alternatively activated, reparatory phenotype. In turn, alternatively activated macrophages are necessary for ectopic lesions to vascularize and grow.…”
Section: Discussionmentioning
confidence: 58%
“…In support to this model, the peritoneal fluid of patients with endometriosis interferes with in vitro differentiation of precursors challenged with recombinant cytokines, favoring their differentiation toward macrophages 9 and immature dendritic cells injected into endometriotic mice intraperitoneally actively migrate and infiltrate ectopic endometrial lesions, where they contribute to lesions further development. 49 In conclusion, our findings indicate that the peritoneal environment controls the differentiation of macrophage precursors, committing them toward an alternatively activated, reparatory phenotype. In turn, alternatively activated macrophages are necessary for ectopic lesions to vascularize and grow.…”
Section: Discussionmentioning
confidence: 58%
“…Based on these findings, we assume that the CD11b ϩ cells could be a subset of dendritic cells. Strikingly, dendritic cells have been shown to play an important role in regulation of angiogenesis 34,35 and, similarly to endothelial cells, do use the uPA/Plg system to migrate. 36 Second, we studied the effect of peptide 18 -36 on tumor growth in a chimeric in vivo model by growing human melanoma cells in SCID mice: the human melanoma M24met cells were injected into the right flank of an animal and at the same time an osmotic pump filled with either scrambled peptide or peptide 18-36 was implanted at a distal position in the same flank.…”
Section: Modulation Of Angiogenesis and Tumor Growth By Sm6p/igf2r Anmentioning
confidence: 99%
“…Defects in DCs caused by the immunosuppressive tumor microenvironment result in the accumulation of immature DCs. These immature DCs can promote tumor angiogenesis (28)(29)(30)(31)(32)(33)(34)(35)(36) and suppress T-cell responses (10), thus favoring tumor progression. We observed that blockade of a PI3Kg-integrin a 4 pathway could facilitate CD11c þ DC infiltration and maturation.…”
Section: Discussionmentioning
confidence: 99%